2020
DOI: 10.1016/j.matt.2019.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Associative Learning by Classical Conditioning in Liquid Crystal Network Actuators

Abstract: Aiming toward bioinspired materials whose responsivity evolves depending on their history, we disclose programmable liquid crystal polymer networks that ''learn'' to respond to an initially neutral stimulus (light) after association with an intrinsically effective stimulus (heating). The concept is inspired by the Pavlovian conditioning and enables soft robots that learn to walk, grippers that recognize different irradiation colors, and an artificial Pavlov's dog. This is a step toward actuators that algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 58 publications
0
67
0
Order By: Relevance
“…To achieve associative learning in artificial materials, a memory and mechanisms (logic gates) to trigger and retrieve the memory are indispensable . The behavior of the Pavlovian materials can in some sense be considered as “switching” of the material property, since it requires the memory to be switched on by the simultaneous exposure to two stimuli (in the present case, light + heat).…”
Section: Discussion and Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…To achieve associative learning in artificial materials, a memory and mechanisms (logic gates) to trigger and retrieve the memory are indispensable . The behavior of the Pavlovian materials can in some sense be considered as “switching” of the material property, since it requires the memory to be switched on by the simultaneous exposure to two stimuli (in the present case, light + heat).…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Therein potentiation or depression can be achieved based on the tuning of spiking. In view of the above‐mentioned literature on classical conditioning in artificial systems, we next review the newly identified concept of learning in synthetic materials by programming the material response with classical conditioning algorithm …”
Section: Pavlovian Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the associative learning LCNs, also termed as Pavlovian materials, that "learn" to respond to an initially neutral stimulus only after being trained by an independent stimulus were designed by Priimagi and co-workers, providing unforeseen routes toward self-studying soft robots. [130,131] The principle of a Pavlovian material is shown in Figure 10A. Initially, the material is insensitive to stimulus 2 but responds to stimulus 1.…”
Section: Associative Learning Lcns For Self-studying Soft Robotsmentioning
confidence: 99%